2018
DOI: 10.1016/j.jenvp.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Low Carbon Readiness Index: A short measure to predict private low carbon behaviour

Abstract: This paper presents a theoretical argument that low carbon strivings -personal goals to reduce carbon footprint in the household -can predict a wide range of diverse behaviours to reduce greenhouse gas emissions, and reports four studies to validate Low Carbon Readiness Index (LCRI), a short, three-item measure of low carbon strivings. It is a simple and easy-to-use indicator of the general public's readiness to transition to a fully low carbon lifestyle. LCRI is associated with validated measures predicting e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…Several studies, for example O'Brien et al ( 2018 ), contained multiple relevant “outcome variables” (i.e., environmental behavior, environmental intention, or environmental attitude, see Inclusion Criteria ) or multiple measures of social desirability (e.g., Haws et al, 2014 ). To ensure independence of observations included in a meta-analysis (Hunter and Schmidt, 1990 ), we therefore conducted three separate meta-analyses, with each of the outcome variables (intention, behavior, and attitude) studied separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies, for example O'Brien et al ( 2018 ), contained multiple relevant “outcome variables” (i.e., environmental behavior, environmental intention, or environmental attitude, see Inclusion Criteria ) or multiple measures of social desirability (e.g., Haws et al, 2014 ). To ensure independence of observations included in a meta-analysis (Hunter and Schmidt, 1990 ), we therefore conducted three separate meta-analyses, with each of the outcome variables (intention, behavior, and attitude) studied separately.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, social desirability has been often viewed as a potential confounding variable in environmental psychology research (Kaiser et al, 1999 ; Bruni and Schultz, 2010 ; Cerri et al, 2019 ). On the other hand, there is also evidence suggesting that social desirability may only play a relatively minor role (e.g., Milfont, 2009 ; O'Brien et al, 2018 ; see also McGrath et al, 2010 ; Paunonen and LeBel, 2012 ). The task of the present meta-analyses is therefore to systematically evaluate existing research on the links between social desirability and various key measures used in environmental psychology studies, in particular self-reported behavior, intention, and a number of general attitudinal measures like the New Environmental Paradigm (Dunlap and Van Liere, 1978 ; Dunlap et al, 2000 ) and connectedness to nature (Mayer and Frantz, 2004 ; Tam, 2013a ).…”
Section: Introductionmentioning
confidence: 99%
“…Participants’ striving to reduce carbon emission was measured with the 3‐item Low Carbon Readiness Index (O’Brien et al, 2018). Agreement was given on items such as “I work hard to reduce my greenhouse gas emissions whenever possible” on a scale of 1 ( strongly disagree ) to 5 ( strongly agre ), α = .78 ( M = 3.52, SD = 0.67).…”
Section: Methodsmentioning
confidence: 99%
“…Heider listed similarity and causality as examples, and we believe that identification is one such relation. Environmental identity can be an explicit proposition about one’s self in relationship with nature, such as connectedness to nature (Mayer & Frantz, 2004), environmentalist identity (EI) (van der Werff, Steg, & Keizer, 2013, 2014b; Whitmarsh & O'Neill, 2010), and environmental striving (ES) (Kashima et al, 2014; O'Brien et al, 2018). Alternatively, it may be an implicit cognitive association between the self and the natural environment.…”
Section: Signs and Objects: Cultural Artefacts In The Human‐made Envimentioning
confidence: 99%
“…Households who reported the use of auxiliary heating or cooling with visitors in their home preoccupancy [43] now report that this is unnecessary because the thermal comfort of the dwelling is considered suitable, except for those who would normally use it for their own comfort. This has implications for considering the influence of social and societal norms when considering household energy use [69]. The measured range of temperatures in the households living areas over a 3-month period from December 2018 to February 2019 is shown in Figure 4.…”
Section: Ambient Heating and Cooling Practicesmentioning
confidence: 99%